Case report: Recurrent catatonia in a patient with 17p13.3 microduplication syndrome - Querter, Ilya; Schuermans, Nika; Van de Velde, Nele; Geleyn, Cisse; Dheedene, Annelies; Audenaert, Kurt; Baeken, Chris; Callewaert, Bert; Lemmens, Gilbert (Frontiers in Psychiatry, 2025)
Catatonia is a clinically significant syndrome with various etiologies, including genetic factors, that are increasingly recognized. We present a case of recurrent catatonia associated with 17p13.3 microduplication syndrome in a 47-year-old woman with a long-standing history of recurrent depressive episodes. At age 44, she experienced her first episode with psychotic and catatonic features, which required hospitalization. Over the next three years, she had four additional catatonic episodes. Four years after her initial presentation, she was diagnosed with 17p13.3 microduplication syndrome. This case emphasizes the importance of considering genetic testing for patients with recurrent catatonia, particularly those with a comorbid developmental disorder. Given the limited number of cases of 17p13.3 microduplication syndrome reported in the literature, we share these findings to encourage prompt genetic assessment in similar presentations. Clinicians treating patients with catatonia should recognize the prevalence of medical, and particularly genetic, disorders that increase susceptibility to catatonia. Conversely, clinicians working with patients who have genetically based neurodevelopmental syndromes should be aware of the challenges in diagnosing and treating catatonia. By identifying catatonia in this patient population, prompt and targeted interventions that may significantly reduce the disabling effects of catatonia can be initiated. This case also expands the known phenotypic spectrum of 17p13.3 microduplication syndrome and contributes to understanding the genetic factors involved in catatonia, though further research is needed to clarify this association.